Pengaturan Pengelompokan Peserta Didik Pada Lembaga Pendidikan Formal - Ibrahim Ibrahim; Dinda Aisyah Aulidya Putri; Octa Romadhona Putri (Universitas Katolik Widya Karya Malang, 2023)
This study is focused on setting the grouping of students in formal educational institutions and the rules that apply to student groups in formal educational institutions. This type of research is library research. Literature review research is the result of analyzing various conceptual information as well as qualitative and quantitative data from various previously published scientific articles. The method used in this research is literature study which serves as a guide in studying a research problem. Based on the results of data analysis, it appears that the grouping of students in formal educational institutions is grouped according to predetermined rules. Grouping students is an important thing to do as part of being able to place students in the right position according to the character, interests and talents of the students. The purpose of grouping students is to facilitate students in the learning process.